Antimicrobial oral lavage reduces the SARS-CoV-2 load in intubated patients: randomized clinical trial - Letícia Mello Bezinelli; Luciana Corrêa; Stephany Beyerstedt; Érika Bevilaqua Rangel; Carlos Benitez; Nelson Hamerschlak; João Renato Rebello Pinho; Debora Heller; Fernanda de Paula Eduardo (Journal of Oral Microbiology, 2023)
ABSTRACTBackground The oral cavity can be a reservoir for SARS-CoV-2 and may play a crucial role in the viral transmission in the hospital environment.Objective To investigate whether an oral hygiene protocol with chlorhexidine (CHX) used alone and in combination with hydrogen peroxide (HP) in the intensive care unit was effective in reducing the SARS-CoV-2 viral load in the oral cavity.Methods SARS-CoV-2 viral load was measured on oral fluid samples collected from patients undergoing orotracheal intubation. The study sample was randomly in: CHX group (n = 19) - oral rinse using only 0.12% CHX solution; HP+CHX group (n = 24) - oral rinse with 1.5% HP and 0.12% CHX. The samples were collected before the interventions (T0), immediately (T1), 30 minutes (T2) and 60 minutes (T3) after the procedure.Results A significant viral load reduction was observed at T1 (mean ± SD:–0.57 ± 0.19 log10;–73.2%;p = 0.022) in the HP+CHX group. No statistically significant differences between any time points were observed in the CHX group.Conclusion The HP+CHX oral rinses significantly reduced the SARS-CoV-2 viral load in the oral fluid immediately after the procedure. The CHX oral rinse alone did not result in any significant viral load reductions.